Formation damage in horizontal and deviated wells - Ismail, Issham; Teow, Ket Seang (Penerbit UTM Press, 2008)
This technical paper discusses the effect of formation damage in horizontal and deviated wells. In general, different drilling environments, such as horizontal drilling and high angle well drilling, will cause different degree of damages which can bring to the reduction of oil productivity. The experimental results revealed drilling in the horizontal environment was the most critical and could cause severe damage to the formation, followed by the high angle well drilling environment. To minimize this problem, the most suitable measure is to understand the most appropriate differential pressure, annular velocity between the drill pipe and bore hole, and the effect of temperatures.